The relationship between mobile online gameplay duration and sleep quality in the latest adolescents - Gede Ariantika Putra; Ari Wibawa; Ni Komang Ayu Juni Antari; I Made Niko Winaya (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: One of adolescents' popular physical activities and entertainments is playing online games. Playing online games with excessive duration can cause poor sleep quality. This study aimed to determine whether there is a relationship between the duration of playing mobile online games with sleep quality in late adolescents at senior high school 1 Dawan, Bali, Indonesia. Methods: The research method used is analytic observational with a cross-sectional design and purposive sampling method. The total sample obtained is 91 samples according to the specified criteria. Data were collected by measuring the duration of playing player unknown's battlegrounds (PUBG) mobile with a questionnaire on the duration of playing online games and measuring sleep quality with the pittsburgh sleep quality index (PSQI) questionnaire. Results: Based on the results of testing the data using spearman rho analysis, the results obtained were p= 0.002. Conclusion: Based on the study's results, it can be concluded that there is a relationship between the duration of mobile online games and sleep quality in late adolescents.